The Prospective Researches as Approach in Planning for Development in New Urban Communities - Alrahman, Abd Alrahman Ali Abd (European Scientific Journal, ESJ, 2019)
The purpose of this study is to identify the relationship between Prospective Researches and planning for social, economic, environmental and health development in new urban communities. The study used a comprehensive social survey for the employees of the new city of Assiut Governorate, which has 300 employees. The researcher used 100 members of the study community to verify the validity and consistency of the tool used in the study. The study was conducted in the hope of studying the relationship between uses of prospective researches and planning for the development of new urban communities in Assiut Governorate. The study included the employees of the new city of Assiut, which has 300 employees. The selection of participants was based on comprehensive Social survey techniques. The data were collected in 2018. The researcher created a model with an introduction letter. He then asked all participants to fill out this letter with the title of study, nature, purpose and name of the participant. The data collection period lasted about 25 days. The results of the study indicate that a strong positive relationship expected between Prospective Researches and planning for social, economic, environmental and health.